A fatherless South Africa: The importance of missional parenting and the role of the church - Freeks, Fazel E. (HTS teologiese studies, 2022)
This article employs descriptive and explorative methods concerning father absence and missional parenting. It identifies numerous ramifications caused by father absence and the failing role of men. Father absence has been a serious social issue in South Africa, which has become more tenacious in post-colonial South Africa because of economic reasons, untold fatherhood, refused fatherhood, fatherhood accountability, divorce and dissolution of households. This social issue influenced and affected both family and society dysfunction and created a vicious cycle of poverty in many South African homes. This article aimed to lessen the predicament of fatherlessness by considering the role of missional parenting where the father and mother form a partnership and collaborate for the family’s progress and actualise God’s pre-eminent plan for families in South Africa. The literature review and methodology provided rich insights and considerable knowledge to help support families who do not have a father figure and men in their fatherly role. Missional parenting is gospel-centred and can be a detriment to father absence. Parents follow the example of Jesus Christ as saviour in missional parenting.Contribution: This article employed a descriptive and explorative modus operandi and explored a respective method to effectuate family disharmony in the context of South Africa. It endorses the journal’s focus on church and family in the field of Missiology and Practical Theology. A fatherless South Africa because of the social ill of father absence is a concerning issue.